2012
DOI: 10.1111/j.1365-2028.2012.01326.x
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐annual variation of the spatiotemporal distribution and abundance of Talitridae and Oniscidea (Crustacea, Peracarida) at Bizerte Lagoon (northern Tunisia)

Abstract: During 1 year from spring 2007 to winter 2008, we conducted four seasonal samplings along a transect in the supralittoral zone of Bizerte Lagoon at Menzel Jmil (Tunisia) to study the intra‐annual variation of Peracarida diversity, Talitridae and Oniscidea. For each season, one transect was studied and quadrates were placed successively from the shoreline to the road backing the shore. Talitridae and Oniscidea were the most abundant taxa in our samples reaching highest densities in summer, when fourteen species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Many studies are interested to this family which plays an important ecological role as decomposers of organic matter and are considered as bioindicators of the quality of sandy beach (Griffiths et al 1983;Ketmaier et al 2003). This role was estimated by genetic (De Matthaeis et al 1994, 1995, 1996, 1998Scapini et al 1995;Bulnheim & Schwenzer 1999;Bouslama et al 2001;Ketmaier et al 2003;Bouslama 2009), reproduction, and spatio-temporal distribution Scapini et al 1999;Charfi-Cheikhrouha et al 2000;Gonçalves et al 2003;Marques et al 2003;Bouslama et al 2007;Gambineri & Scapini 2008;Jelassi et al 2012;Jelassi, Zimmer et al 2013), as well as behavioral approaches (Scapini et al 1993;Scapini 1997;Nasri-Ammar & Morgan 2005, 2006Rossano et al 2008, Ayari & Nasri-Ammar 2012a, 2012bJelassi, Akkari-Ayari et al 2013;.…”
Section: Please Scroll Down For Articlementioning
confidence: 98%
“…Many studies are interested to this family which plays an important ecological role as decomposers of organic matter and are considered as bioindicators of the quality of sandy beach (Griffiths et al 1983;Ketmaier et al 2003). This role was estimated by genetic (De Matthaeis et al 1994, 1995, 1996, 1998Scapini et al 1995;Bulnheim & Schwenzer 1999;Bouslama et al 2001;Ketmaier et al 2003;Bouslama 2009), reproduction, and spatio-temporal distribution Scapini et al 1999;Charfi-Cheikhrouha et al 2000;Gonçalves et al 2003;Marques et al 2003;Bouslama et al 2007;Gambineri & Scapini 2008;Jelassi et al 2012;Jelassi, Zimmer et al 2013), as well as behavioral approaches (Scapini et al 1993;Scapini 1997;Nasri-Ammar & Morgan 2005, 2006Rossano et al 2008, Ayari & Nasri-Ammar 2012a, 2012bJelassi, Akkari-Ayari et al 2013;.…”
Section: Please Scroll Down For Articlementioning
confidence: 98%
“…Talitrid amphipods represent one of the prevailing macrofaunal groups in sandy beaches (Dahl 1946;McLachlan & Jaramillo 1995) and other wetlands (Jelassi et al, 2012, Jelassi et al, 2013a, 2013b. These supralittoral decomposers of biological debris are regarded as a potential bio-indicator of the quality of sandy beaches (Griffiths et al 1983;Ketmaier et al 2003).…”
Section: Introductionmentioning
confidence: 98%
“…Several studies were focused on the role of environmental factors and showed the influence of factors than others Scapini et al 1995;Scapini and Fasinella 1990;Scapini et al 1999;Scapini and Quochi 1992). Jelassi et al (2012) showed that Talitridae abundance was tightly controlled by air temperature. The highest abundance observed in this site could be also explained by the important recruitment in spring (Jelassi 2014).…”
Section: )mentioning
confidence: 99%
“…In Tunisia, amphipod communities inhabiting the supralittoral zone of wetlands, other than sandy beaches (Jelassi and Nasri-Ammar 2013;Jelassi et al 2012;Jelassi et al 2013a), have not received much attention. Thus, aims of this study were to produce a list of amphipod species collected in the supralittoral zones of different lagoons, to estimate species richness, abundance, and density, and we focus on environmental factors that may control their spatial distribution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation